PENGARUH CORPORATE GOVERNANCE DAN RASIO UTANG TERHADAP EARNINGS MANAGEMENT - I Gusti Ngurah Bagus Gunadi (Forum Manajemen STIMI Handayani Denpasar, 2016)
Earnings management is management actions in the process of preparationof financial statements to affect the level of reported earnings. Earnings managementcan reduce the credibility of the financial statements if it is used to make decisions,because earnings management is a form of manipulation of financial statements.This study aimed to examine the effect of corporate governance and leverage toearnings management. The sample in this study were 81 companies listed on theIndonesian Stock Exchange for the period 2011-2013. Sampling using purposivesampling method. The analysis technique used in this study is factor analysis andmultiple linear regression analysis. The results showed that the variables of corporategovernance negatively affect earnings management. While the variable leverage apositive effect on earnings management.